2018
DOI: 10.1038/s41598-018-23072-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sarcosine as a Target Molecule for the Canine Olfactory Detection of Prostate Carcinoma

Abstract: The hypothesis that dogs can detect malignant tumours through the identification of specific molecules is nearly 30 years old. To date, several reports have described the successful detection of distinct types of cancer. However, is still a lack of data regarding the specific molecules that can be recognized by a dog’s olfactory apparatus. Hence, we performed a study with artificially prepared, well-characterized urinary specimens that were enriched with sarcosine, a widely reported urinary biomarker for prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Although the measurements in blood have been reported as unremarkable, significantly elevated levels in urine have been recorded in some studies, for patients with prostate cancer. Furthermore, in a recent study cancer sniffer dogs were able to distinguish artificial urine samples that had been doped with sarcosine, with 90% success rate [17]. The possible role of sarcosine is however still strongly debated [18], but some recent studies have suggested that sarcosine exhibits considerable stimulatory effects on growth in malignant/metastatic prostate cells [19], possibly due to accumulation in the tumor and consequential conversion to serine and glycine, thereby providing tumor growth promoters [20,21].…”
mentioning
confidence: 99%
“…Although the measurements in blood have been reported as unremarkable, significantly elevated levels in urine have been recorded in some studies, for patients with prostate cancer. Furthermore, in a recent study cancer sniffer dogs were able to distinguish artificial urine samples that had been doped with sarcosine, with 90% success rate [17]. The possible role of sarcosine is however still strongly debated [18], but some recent studies have suggested that sarcosine exhibits considerable stimulatory effects on growth in malignant/metastatic prostate cells [19], possibly due to accumulation in the tumor and consequential conversion to serine and glycine, thereby providing tumor growth promoters [20,21].…”
mentioning
confidence: 99%
“…However, these results remain controversial, according to various follow-up studies in different PCa cohorts [ 50 ]. Moreover, many groups have attempted the development of methods to monitor sarcosine abundance [ 51 53 ], and combination of sarcosine with other metabolites has been tested in order to test its prognostic potential [ 54 ]. The opposed regulation of GNMT expression by AR vs .…”
Section: Discussionmentioning
confidence: 99%
“…We propose seven plasma metabolites as potential melanoma biomarkers, including beta-alanine, p -cresol sulfate, sarcosine, tiglylcarnitine, Hex2Cer (d18:1/16:0), Hex2Cer (d18:1/20:0), and PC ae C42:4, to distinguish healthy from melanoma-bearing mice. Of those seven metabolites, sarcosine is a well-established urine biomarker for prostate cancer [ 54 , 55 , 56 ]. However, to our knowledge, sarcosine has not yet been reported as biomarker for melanoma.…”
Section: Discussionmentioning
confidence: 99%